The Construction and Exploration of a Comprehensive MicroRNA Centered Regulatory Network in Foxtail Millet (Setaria italica L.) - Deng, Yang; Zhang, Haolin; Wang, Hailong; Xing, Guofang; Lei, Biao; Kuang, Zheng; Zhao, Yongxin; Li, Congcong; Dai, Shaojun; Yang, Xiaozeng; Wei, Jianhua; Zhang, Jiewei (Frontiers in Plant Science, 2022)
MicroRNA (miRNA) is an essential endogenous post-transcriptional regulatory factor, and foxtail millet (Setaria italica L.) is an ideal C4 model cereal that is a highly valuable crop in semiarid and arid areas. The Research on comprehensive and high confidence identification and annotation of foxtail millet miRNAs needs to be strengthened, and to our knowledge, there is no information on the regulatory network of foxtail millet miRNA. In this study, 136 high confidence miRNAs were identified through high-throughput sequencing of the small RNAs in seven tissues at the shooting and grain filling stages of foxtail millet. A total of 2,417 target genes were obtained by combining computational biology software and degradome sequencing methods. Furthermore, an analysis using transcriptome sequencing revealed the relationships between miRNAs and their target genes and simultaneously explored key regulatory modules in panicles during the grain filling stage. An miRNA regulatory network was constructed to explore the functions of miRNA in more detail. This network, centered on miRNAs and combining upstream transcriptional factors and downstream target genes, is primarily composed of feed forward loop motifs, which greatly enhances our knowledge of the potential functions of miRNAs and uncovers numerous previously unknown regulatory links. This study provides a solid foundation for research on the function and regulatory network of miRNAs in foxtail millet.